Opinion formation with time-varying bounded confidence related to the node degree. (March 2019) - Yunhong, Zhang; Qipeng, Liu; Lin, Ding; Siying, Zhang
People like to communicate with others who have similar opinions in daily life. "Open" individuals are willing to accept peers' opinions, whereas "conservative" individuals are more closed to others' opinions. Based on this reality, an opinion dynamic model is proposed with a time-varying trust threshold related to the node degree, which refers to the number of individuals that can be communicated directly. Similar opinions within the trust thresholds at the beginning will eventually form a consensus opinion. Individuals who have common neighbors converge to consensus faster than ones who have no common neighbors. The network size impacts the convergent speed of the opinion cluster and the trust threshold cluster. Individuals in small groups are more stressed than in large ones when they try to insist their opinions. A group with half of the individuals categorized as doubting and the other half categorized as trusting exhibits consistent confidence but experiences difficulty in reaching a consensus: "harmony but difference" may be a criterion for unifying a group.